Personality and Coping Individual Differences in Responses to Emotion. [article]. - Segerstrom, Suzanne C.
Abundant evidence links personality with emotion via coping. Alternatively, personality can be viewed as an emergent property of responses to the experience of emotion. Dispositions to control, approach, escape, and avoid one's emotional experience underlie diverse traits, including positive and negative urgency, trait emotional approach and avoidance, alexithymia, and emotional expressiveness. In this review, we consider the neurobiological underpinnings of these dispositions and the nature (e.g., stability) and adaptiveness of the associated traits. Important future directions for research in this area include the roles of development, intraindividual variability and flexibility, and the intensity and structure of emotional experience. -- (from the author)